Physical therapy in relation to gait and balance in elderly women - doi:10.5020/18061230.2011.p207 - Anniele Martins Silva; Rosane Batista e Silva; Ricardo Alexandre Guerra; Gisela Rocha de Siqueira (Universidade de Fortaleza, 2012)
Objective: To determine if there is a benefit of physical therapy intervention in relation to balance and gait in the elderly. Methods: An interventional study held in 2009 in Caruaru-PE, Brazil, evaluated elderly women aged 60 and 82 years, randomly divided into two groups, control and intervention, undergoing physical therapy assessment (posture, balance and mobility through Timed Get Up and Go Test scorings- TUG), analysis of socio-demographic profile (age, sex, history of falls, fear of falling, physical activity, smoking and drinking) and physical therapy intervention for 10 weeks. Statistical analysis included chi-square test, Fisher's exact and ANOVA. Results: We found that the risk of falls was more evident in the control group (p <0.05) regarding to the scores and rankings obtained in the TUG test. After the intervention, no participant in the experimental group reported fear of falling, and no longer reported the presence of pain. Conclusion: Physical therapy achieved through stretching exercises and training of balance and strength brought benefits to both the balance and the gait of the studied sample.